High country [large type] - Manning, Jason (High country, 2021)
A young man in a virgin land, a sweeping saga alive with the courage, challenge, danger and adventure that was the American frontier. In 1825 the distant Rockies offered all the adventure and wealth a young man could want. The mad demand for beaver pelts spawned a booming fur trade that sent men to battle against the fury of nature, hostile Indian tribes, and even each other in an ordeal that only the strongest could survive. Zach Hannah was a mere youth when he left the Tennessee hill country to seek his fortune in the West. He faced many challenges-to learn the way of the wild and those who lived in it, to discover that the white man's treachery could be as deadly as Blackfoot hostility. And to find passionate love with a beautiful Indian woman-and fight to the death to protect her.